Algebras of Unbounded Operators over the Ring of Measurable Functions and Their Derivations and Automorphisms - Albeverio, S.; Ayupov, Sh.A.; Zaitov, A.A.; Ruziev, J.E. (Інститут математики НАН України, 2009)
In the present paper derivations and *-automorphisms of algebras of unbounded operators over the ring of measurable functions are investigated and it is shown that all Lº-linear derivations and Lº-linear *-automorphisms are inner. Moreover, it is proved that each L0-linear automorphism of the algebra of all linear operators on a bo-dense submodule of a Kaplansky-Hilbert module over the ring of measurable functions is spatial.